Integrating Arabic Language, Sociological Perspectives and Physical Education in Fostering Green Practices in the Maritime Industry - Shittu, Morufudeen Adeniyi; Adeyemo, Eniola Abioye; Yusuf, Taofeek Olalekan; Arinla, Shakirullah Muhammed (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026, 2026)
The significance of fostering green practices in the maritime industry lies in the need to address environmental concerns and promote sustainable development. Green practices can help reduce carbon emissions, minimize pollution, and protect marine ecosystems. To achieve this purpose, this study examines the integration of Arabic language, sociological perspectives, and physical education in fostering green practices within the maritime industry in Lagos State, Nigeria. Employing an ex-post facto research design, the study utilized a stratified random sampling technique to select 150 participants from three public tertiary institutions. Data was collected using a validated questionnaire (ALSPPEMIQ) with a reliability coefficient of 0.815. The findings reveal that specific sociolinguistic factors significantly influence decision-making and behavior related to environmental sustainability in the maritime industry. Additionally, existing physical education programs demonstrate effectiveness in promoting environmental awareness and sustainable practices among maritime professionals. The study also found a significant impact of an integrated curriculum (Arabic language, sociological perspectives, and physical education) on the environmental knowledge, attitudes, and behaviors of maritime professionals in Lagos State. These results highlight the importance of a multidisciplinary approach in fostering green practices within the maritime industry. The study concludes that this integrated approach can help in creating a more environmentally conscious workforce and contribute to sustainable development in Lagos State, Nigeria. The Study recommends that there is need to encourage collaboration and partnerships between educational institutions, government agencies, and maritime organizations to support the implementation of green practices in the industry through the integration of language, sociological perspectives, and physical education components. Keywords: Green practices, Arabic language, Maritime industry, Sociological perspective and Physical education